2005
DOI: 10.1021/ac0580058
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Mechanism in RPLC. Effect of the Nature of the Organic Modifier

Abstract: The adsorption isotherms of phenol and caffeine were acquired by frontal analysis on two different adsorbents, Kromasil-C 18 and Discovery-C 18 , with two different mobile phases, aqueous solutions of methanol (MeOH/H 2 O ) 40/60 and 30/70, v/v) and aqueous solutions of acetonitrile (MeCN/H 2 O ) 30/70 and 20/80, v/v). The adsorption isotherms are always strictly convex upward in methanol/water solutions. The calculations of the adsorption energy distribution confirm that the adsorption data for phenol are bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 39 publications
5
76
0
Order By: Relevance
“…14 They constitute a solvent layer, which contacts with the bonded ligand layer. 15,16 Gritti and Guiochon reported the thickness of the adsorbed monolayer of methanol and multilayer of acetonitrile as 0.25 and 1.36 nm, respectively, on C18-silica gels. 15 Similarly, Shibukawa et al reported that the thickness of the solvent layer is 1.6 nm or more in the RPLC system consisting of alkyl bonded silica and 20% (w/v) acetonitrile-water.…”
Section: Peak Parking-moment Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 They constitute a solvent layer, which contacts with the bonded ligand layer. 15,16 Gritti and Guiochon reported the thickness of the adsorbed monolayer of methanol and multilayer of acetonitrile as 0.25 and 1.36 nm, respectively, on C18-silica gels. 15 Similarly, Shibukawa et al reported that the thickness of the solvent layer is 1.6 nm or more in the RPLC system consisting of alkyl bonded silica and 20% (w/v) acetonitrile-water.…”
Section: Peak Parking-moment Analysis Methodsmentioning
confidence: 99%
“…15,16 Gritti and Guiochon reported the thickness of the adsorbed monolayer of methanol and multilayer of acetonitrile as 0.25 and 1.36 nm, respectively, on C18-silica gels. 15 Similarly, Shibukawa et al reported that the thickness of the solvent layer is 1.6 nm or more in the RPLC system consisting of alkyl bonded silica and 20% (w/v) acetonitrile-water. 16 It seems that some physico-chemical properties of the solvent layer are different from those of the bulk mobile phase.…”
Section: Peak Parking-moment Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the adsorption of ACN on hydrophobic stationary phase is much stronger than the adsorption of methanol [38]. On the contrary, significant amount of methanol may be adsorbed near the silica surface through the hydrogen bonding with residual accessible silanols.…”
Section: Influence Of the Organic Modifiermentioning
confidence: 99%
“…As was mentioned by Gritti and Guiochon (2005a), the type of the organic modifier has a big influence on the adsorption and retention of the solute. The retention and the elution in the chromatographic system is a competitive play between solute and organic modifier.…”
mentioning
confidence: 96%